2021
DOI: 10.3389/fonc.2021.753788
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 2 Gene Polymorphisms Are Associated With Lung Adenocarcinoma Risk in Female Never-Smokers

Abstract: ObjectivesLung cancer in never-smokers is a distinct disease associated with a different genomic landscape, pathogenesis, risk factors, and immune checkpoint inhibitor responses compared to those observed in smokers. This study aimed to identify novel single nucleotide polymorphisms (SNPs) of programmed death-1 (encoded by PDCD1) and its ligands, programmed death ligand 1 (CD274) and 2 (PDCD1LG2), associated with lung cancer risk in never-smoking women.Materials and MethodsDuring September 2002 and July 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…TB infection can aggravate chronic inflammation, which may not only weaken the innate and acquired immune responses, but may also be related to the abnormal expression of immune-associated genes [ 96 ]. Tuberculosis infection, chronic obstructive pulmonary disease (COPD), smoking and cooking fume exposure, are defined as chronic inflammation-associated environmental exposures, and the interaction between these exposure factors and single nucleotide polymorphisms (SNPs) in lung cancer susceptibility has also been highly valued by researchers [ 97 ]. In this study, tuberculosis infection was an environmental exposure related to the risk of lung adenocarcinoma in women who had never smoked.…”
Section: Expression Of Inhibitory Receptors In Pulmonary Tuberculosis...mentioning
confidence: 99%
See 1 more Smart Citation
“…TB infection can aggravate chronic inflammation, which may not only weaken the innate and acquired immune responses, but may also be related to the abnormal expression of immune-associated genes [ 96 ]. Tuberculosis infection, chronic obstructive pulmonary disease (COPD), smoking and cooking fume exposure, are defined as chronic inflammation-associated environmental exposures, and the interaction between these exposure factors and single nucleotide polymorphisms (SNPs) in lung cancer susceptibility has also been highly valued by researchers [ 97 ]. In this study, tuberculosis infection was an environmental exposure related to the risk of lung adenocarcinoma in women who had never smoked.…”
Section: Expression Of Inhibitory Receptors In Pulmonary Tuberculosis...mentioning
confidence: 99%
“…A new SNP for PDCD1LG2 related to lung adenocarcinoma risk has been identified. Among them, two SNPs related to susceptibility to lung adenocarcinoma are related to tuberculosis infection [ 97 ]. Cao et al analyzed the expression levels and function of PD-1, PD-L1, and PD-L2 in antigen-specific T cells from Mycobacterium tuberculosis patients and spleen lymphocytes from wild type and PD-1 knockout mice, and Lewis mice injected with lung cancer cells.…”
Section: Expression Of Inhibitory Receptors In Pulmonary Tuberculosis...mentioning
confidence: 99%
“…These characteristics may help explain why NSCLC adenocarcinomas in never smokers typically do not demonstrate durable responses with immune checkpoint blockade despite PD-L1 expression (smokers have a higher PD-L1 expression) ( 56 ). Interestingly, PD-L2 gene (PDCD1LG2) single nucleotide polymorphisms (SNPs) are associated with lung adenocarcinoma risk in female never-smokers, and 3 of these SNPs were negatively associated with PD-L2 expression in non-tumor tissue, but not in tumor tissue ( 57 ). Although PD-L1 expression has been shown to be associated with carcinogenesis, tumor differentiation and vascular invasion, the role of PD-L2 is still poorly explored.…”
Section: Immune Landscape In Never-smoker Lung Cancer Patientsmentioning
confidence: 99%
“…Although PD-L1 expression has been shown to be associated with carcinogenesis, tumor differentiation and vascular invasion, the role of PD-L2 is still poorly explored. Mechanistically, at low antigen concentrations the interaction between PD-L2 and PD-1 inhibits strong B7-CD28 signals, while at high concentrations, the interaction between PD-L2 and PD-1 reduces cytokine production, but not T cell proliferation, but the correlation between these PDCD1LG2 SNPs and PD-L2 expression requires further investigation, which might provide further insight into the PD-1/PD-L2 axis in T cell function and lung carcinogenesis ( 57 ).…”
Section: Immune Landscape In Never-smoker Lung Cancer Patientsmentioning
confidence: 99%
“…Smoking is a major risk factor for lung carcinogenesis 2 ; however, about a quarter of lung cancer cases are not related to smoking, and it is reported that more than half of female patients never smoke. 3 Furthermore, the number of LUAD in female never smokers is gradually increasing. 4 , 5 Non-smoking females with LUAD account for a unique disease entity, showing different pathogenesis, epidemiological characteristics and course of disease.…”
Section: Introductionmentioning
confidence: 99%